Short-term corneal response to corneal refractive therapy for different refractive targets - Villa-Collar, Cesar (2009)
Purpose: The goal of the present study was to investigate the short-term variations in corneal topography within the first 3 hours of lens wear under open eye conditions, which call be considered an off-label condition in current orthokeratology treatment, and the recovery of the effect during an additional 3-hour period after lens removal.Methods: Fourteen Volunteers were fitted with Paragon CRT reverse geometry rigid gas permeable contact lenses Simulating 2 different refractive targets of -2.00 and -4.00 diopters of myopia correction in the right and left eyes in random order. After the lenses were placed in both eyes. Subsequent measurements of corneal topography were obtained at 30, 60, and 180 minutes: the same measurements were also taken at 30, 60, and 180 minutes after lens removal.Results: Significant flattening of the cornea was evident after 30 minutes of lens wear. Overall, the -4.00 group changes progressed more rapidly than in the -2.00 group, and they also took more time to recover after lens removal. However, for most of the parameters, differences between -2.00 and -4.00 treatments are evident only after 60 minutes of lens wear.Conclusions: Under open eye conditions, the first 30 minutes of corneal refractive therapy are determinant to establish the myopic orthokeratologic effect and changes are almost identical irrespective of the refractive target. After this point, changes are different depending on the refractive target. The recovery was almost as fast as the onset of the orthokeratologic effect, demonstrating that the cornea deforms quickly beneath these lenses and does recover safely and quickly once the lenses are removed.